A preparation method and application of porous structure nano-ceramics

By using porous structured nano -ceramics in lithium ion batteries as diaphragm materials, the battery performance decline caused by transition metal ion impurities has been solved, and the battery performance is improved.

CN118834061BActive Publication Date: 2025-01-28SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411310912.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-28
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The presence of transition metal ion impurities in lithium-ion batteries leads to degradation of battery performance, including increased internal resistance, increased polarization, loss of positive and negative electrode active substances and lithium losses.

Method used

The porous structure nano -ceramic is used as a battery diaphragm material. It is prepared through the steps of precipitation, drying and burning to form a porous structure with adsorption transition metal ions.

Benefits of technology

Effectively reduce the transmission and sedimentation of transition metal ions, and improve the energy density, cycle life and security of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118834061B_ABST
    Figure CN118834061B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery materials, and specifically provides a method for preparing a porous structure nano-ceramic and its application, which comprises a precipitation step of precipitating a template molecule and a metal salt in a solution to generate a metal precipitate; a drying step of drying the metal precipitate to obtain a metal dried product; and a calcining step of calcining the metal dried product in an oxygen atmosphere to obtain a porous structure nano-ceramic. When the porous structure nano-ceramic provided by the present invention is used as a battery separator material, it has the effect of improving the metal ion adsorption force and ion conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to a preparation method and application of porous structure nano-ceramics. Background Art

[0002] With the increasing development of 3C electronic products and new energy industries, the requirements for battery performance are also increasing. The indicators that will be evaluated on battery performance include energy density, battery capacity, cycle life, and safety. The above indicators are greatly affected by the characteristics, properties, composition or combination of each component in the battery.

[0003] Regarding the issue of battery capacity, it is generally believed that the main factors for battery capacity degradation include: increased internal resistance, increased polarization, loss of positive and negative electrode active materials, and lithium loss; and in the process of battery preparation, the positive and negative electrodes or the separator electrolyte will inevitably be doped with transition metal impurities such as aluminum, iron, and nickel, which have a reduction potential lower than that of lithium; these metal ions with a reduction potential lower than that of lithium will be embedded in the graphite negative electrode during the charging process, thereby reducing the position where lithium ions can be embedded in the negative electrode, reducing the reversible capacity of the lithium battery, and in addition, the precipitation of these metal ions on the surface of the graphite negative electrode will result in the inability to form an effective passivation layer on the surface of the graphite electrode, causing further irreversible damage to the battery. Therefore, it can be understood that if the effects of transition metal ion impurities can be removed or reduced, the performance of the battery will be significantly improved. Summary of the invention

[0004] There are several strategies for removing transition metal impurities from the aforementioned lithium-ion batteries, including: 1. Selecting suitable positive and negative electrode materials, such as optimizing the composition structure of positive and negative electrode materials to reduce the dissolution or precipitation of transition metal ions; 2. Adjusting to a suitable electrolyte, including adjusting the lithium salt concentration, adding passivators or chelating agents, etc., to reduce the dissolution and migration of transition metal ions; 3. Adding capture agents, introducing specific additives or adsorbents, which can selectively capture transition metal ions; 4. Introducing ion exchange membranes to selectively block the transmission of transition metal ions; 5. Removing transition metal ions from the battery by cleaning or regenerating the electrolyte and battery materials; 6. Improving the diaphragm, by optimizing the structure and materials of the diaphragm, the diaphragm will be able to have the effect of blocking transition metal ions.

[0005] In order to optimize the diaphragm structure and materials of the battery and reduce the influence of transition metal ions on the battery performance, the present invention provides a porous structure nano-ceramic.

[0006] First, the present invention provides a method for preparing a porous structure nano-ceramic, comprising the following steps: a precipitation step: precipitating a template molecule and a metal salt in a solution to generate a metal precipitate; a drying step: drying the metal precipitate to obtain a metal dried product; and a calcining step: calcining the metal dried product, which comprises: calcining the metal dried products in sequence in an oxygen atmosphere to obtain the porous structure nano-ceramic, which comprises: a first calcination: calcining the metal dried product at a first calcination temperature for a first calcination time; a second calcination: calcining the metal dried product at a second calcination temperature for a second calcination time; wherein the first calcination temperature is lower than the second calcination temperature, and the first calcination time is equal to or less than the second calcination time.

[0007] In some preferred embodiments of the present invention, the calcination step further includes a third calcination, which is subsequent to the second calcination: the metal dried product is calcined at a third calcination temperature for a third calcination time in a carbon dioxide atmosphere, wherein the third calcination temperature is greater than the second calcination temperature, and the third calcination time is less than the second calcination time.

[0008] In some preferred embodiments of the present invention, the template molecule includes: nanographite or nanocarbon tube.

[0009] In some preferred embodiments of the present invention, the template molecules further include spherical template molecules and / or linear template molecules, wherein the diameter of the spherical template molecules is 2-50 nanometers, and the length of the linear template molecules is 0.1-2 micrometers.

[0010] In some preferred embodiments of the present invention, the metal salt is selected from one or more of the following: aluminum salt, calcium salt, magnesium salt, barium salt or zirconium salt; in some preferred embodiments, the metal salt is a metal chloride salt, a metal oxide salt, a metal nitrate salt or any combination thereof; in some further preferred embodiments, the metal salt is aluminum chloride, calcium chloride, zirconium nitrate or any combination thereof.

[0011] In some more preferred embodiments of the present invention, the mass ratio of the template molecule to the metal salt is 1:(500-5000), preferably 1:(1000-4500).

[0012] In some preferred embodiments of the present invention, the pH value of the solution in the precipitation step is 7-12, preferably 7.5-10.

[0013] In some preferred embodiments of the present invention, the first calcination temperature is 100-300°C, the first calcination time is 0.5-3 hours, the second calcination temperature is 400-800°C, the second calcination time is 2.5-8 hours, the third calcination temperature is 800-1000°C, and the third calcination time is 0.25-2 hours.

[0014] The present invention further provides a coating slurry, which comprises the porous structure nano-ceramic.

[0015] The present invention further provides a battery separator, which includes: a ceramic layer, wherein the ceramic layer has the porous structure nano-ceramic.

[0016] The present invention further provides a battery, which comprises the battery separator.

[0017] Compared with the prior art, the beneficial effect of the present invention is that the porous structure of the porous structure nanoceramic has the ability to adsorb transition metal ions. In detail, the type of metal salt provides a qualitative effect for the porous structure nanoceramic, and the template molecule is used by the porous structure nanoceramic to create a porous structure, and the size of the pores is also regulated by the size of the template molecule; then, the third calcination can further improve the ion conductivity; further, the porous structure nanoceramic, when used as a coating slurry and a battery separator, will further boost the performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 , is a flow chart for preparing porous structure nanoceramics in a preferred embodiment of the present invention.

[0019] Figure 2 , is a flow chart for preparing the coating slurry in a preferred embodiment of the present invention.

[0020] Figure 3 , is a flow chart for preparing a battery separator in a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0021] In order to make the purpose, effect and features of the present invention easier to understand, only a few preferred embodiments are listed in all the embodiments, and the present invention is described in detail in conjunction with the relevant drawings; in addition, the experiments or test conditions mentioned below that are not specifically marked or cited are performed based on conventional knowledge or methods.

[0022] First, please refer to Figure 1In some preferred embodiments of the present invention, the present invention provides a method for preparing a porous structure nanoceramic 141, comprising the following steps: a mixing step S11: mixing a template molecule 01 with a metal salt solution 02 to obtain a mixed solution 111; a precipitation step S12: adjusting the mixed solution 111 to a pH value to generate a metal precipitate 121 in the mixed solution 111; a drying step S13: drying the metal precipitate 121 to obtain a metal dried product 131; and a calcining step S14: calcining the metal dried product 131, which comprises: calcining the metal dried product 131 at a first calcining temperature for a first calcining time (first calcining S141), then calcining at a second calcining temperature for a second calcining time (second calcining S142), and optionally calcining at a third calcining temperature for a third time (third calcining S143) to obtain a porous structure nanoceramic 141.

[0023] In some preferred embodiments, the porous structure nano-ceramic 141 is in powder form, and its particle size is about 0.5-30 micrometers (μm).

[0024] In some preferred embodiments, the preparation method of the above-mentioned porous structure nanoceramic 141 can optionally include a crushing step: the porous structure nanoceramic 141 is crushed to obtain a porous structure nanoceramic fine powder; the crushing step is carried out by mechanical means such as roller crushing, roller crushing and air flow crushing.

[0025] In some preferred embodiments of the present invention, please refer to Figure 1 In the mixing step S11, in order to obtain a sufficient mixing effect, a mixing action is further included, and the mixing action includes stirring or ultrasonic vibration, etc. The order of the mixing actions, whether multiple mixing actions are performed simultaneously, or whether there are other mixing actions are not limited; to be more specific, in some preferred embodiments of the present invention, the stirring speed of the stirring step can be 200-3000rpm or 300-3000rpm, and the ultrasonic frequency can be 5-20kz or 10-20kz. It can be understood that the stirring speed or ultrasonic frequency is not limited in their respective ranges.

[0026] In the mixing step S11, the temperature should be such as not to interfere with the mixing of the mixed template molecules 01 or the metal salt solution 02. Specifically, the temperature is between 5-80°C, including the range of 25-80°C or 10-60°C, which is understandable and not limiting.

[0027] In some preferred embodiments of the present invention, please refer to Figure 1, the template molecule 01 includes: nanographite or nanocarbon tube, and in some preferred embodiments of the present invention, the template molecule 01 further includes a spherical template molecule or a linear template molecule, wherein the diameter of the spherical template molecule is 2-50 nanometers, and the length of the linear template molecule is 0.1-2 micrometers; it can be understood that the template molecule 01 here provides a template function, and the type and shape of the template molecule 01 are not particularly limited, and many other template molecules 01 can be used. It can also be further understood that the template molecule 01 should be able to be removed in subsequent steps. In addition, the size of the template molecule 01 is nanometer or micrometer.

[0028] In some preferred embodiments of the present invention, please refer to Figure 1 The metal component of the metal salt solution 02 can be selected from one or more of the following: aluminum, calcium, magnesium, barium or zirconium, but not limited thereto, and can be made into a metal salt solution 02 by combining several metals, for example, a salt solution with a certain ratio of calcium and barium. In some preferred embodiments of the present invention, the mass ratio of the template molecule 01 to the metal salt is 1:(14.8-4500), preferably 1:(1700-4500).

[0029] In some preferred embodiments of the present invention, the metal salt solution 02 may be an oxidized metal salt solution, a chloride metal salt solution or a nitrate metal salt solution; however, in some embodiments, the metal salt is not particularly limited in its matching partner.

[0030] In some preferred embodiments of the present invention, in the mixing step S11, the concentration of the metal salt solution 02 is prepared to be 0.01-10 mol / L before mixing with the template molecule 01.

[0031] In some preferred embodiments of the present invention, please refer to Figure 1 , in the precipitation step S12, the pH value is 7-12, preferably 7.5-10. To adjust the pH value, a pH adjuster can be used in some preferred embodiments, wherein the pH adjuster can be selected from one or more of the following components, including: sodium hydroxide, sodium bicarbonate, ammonia, ethylenediamine, ethanolamine, acetic acid or hydrochloric acid. By adjusting the pH value to the ideal range, the metal ions contained in the mixed solution 111 can be precipitated to form the metal precipitate 121, which can be collected or subjected to subsequent actions. In some preferred embodiments of the present invention, the liquid portion can be removed by filtering to retain the desired metal precipitate 121.

[0032] In the precipitation step S12, the precipitation temperature can be 5-60°C, the precipitation reaction time can be 5-30 minutes, the stirring speed can be 200-3000rpm, and the ultrasonic frequency can be 5-10kz. It can be understood that the precipitation temperature, stirring speed or ultrasonic frequency are within their respective data ranges and are not limited.

[0033] In some preferred embodiments of the present invention, in the drying step S13, a drying device is used to dry the metal precipitate 121 at a drying temperature for a drying time to obtain the metal dried product 131, wherein the drying device includes a blast drying oven, the drying temperature is between 30-200°C, and the drying time is not limited, but is preferably 1-24 hours.

[0034] In some preferred embodiments of the present invention, please refer to Figure 1 In the calcination step S14, the first calcination S141 includes the first calcination temperature of 100-300°C, and the first calcination time of 0.5-3 hours; the second calcination S142 includes the second calcination temperature of 400-800°C, and the second calcination time of 2.5-8 hours; the third calcination S143 includes the third calcination temperature of 800-1000°C, and the third calcination time of 0.25-2 hours; it can be understood that the first calcination temperature, the second calcination temperature or the third calcination temperature can achieve the effect within their respective temperature ranges, and similarly, the first calcination time, the second calcination time or the third calcination time can achieve the effect within their respective time ranges, so it is no longer necessary to repeat or list the data item by item.

[0035] In some preferred embodiments of the present invention, in the calcining step S14, there is no strict restriction on the conversion of the calcining temperature, that is, for example, when the first calcination S141 is connected to the second calcination S142, the temperature change rate is not limited. If further described, it is preferably a temperature change rate of 3-20°C per minute. It should be noted that the metal dried object 131 must be kept at least at the first calcination temperature for the first calcination time, and similarly, at the second calcination temperature for the second calcination time, and at the third calcination temperature for the third calcination time, in order to achieve the purpose of calcination and related effects.

[0036] In some preferred embodiments of the present invention, please refer to Figure 1The calcination step S14 can be performed in an oxygen or carbon dioxide atmosphere, which can be used as a mechanism for switching between them. In some embodiments, when graphite is selected as the template molecule 01, it must be calcined in an oxygen atmosphere to remove the graphite. In other embodiments, when graphite is selected as the template molecule 01, the first calcination S141 and the second calcination S142 are first performed in an oxygen atmosphere, and then the third calcination S143 is performed in an oxygen-free, low-oxygen or carbon dioxide atmosphere, wherein the low-oxygen refers to an oxygen concentration lower than the general ground level, or it can be said that the low-oxygen environment is achieved by introducing other gases.

[0037] In addition, it should be noted that in some preferred embodiments of the present invention, please refer to Figure 1 The calcination step S14 has two main purposes. One is to sinter the ceramic particles into a shape through high-temperature calcination. Second, high-temperature calcination is also a means of removing the template molecule 01. By selecting a template molecule 01 that can be removed through high-temperature calcination, such as graphite, a porous structure nanoceramic 141 with a porous structure can be obtained in this calcination step S14.

[0038] It is worth adding that before performing the calcination step S14, it is conceivable that during the process, the ceramic particles may be coated with graphite to produce a transitional coating structure, which may be a capsule structure or a core-shell structure; after performing the calcination step S14, since the graphite has been removed, the ceramic particles will produce a porous structure, and the porous structure includes a porous structure on the surface of the ceramic particles, and the porous structure may also extend to the interior of the ceramic particles, so that a similar hollow structure is formed inside the ceramic particles; at the same time, it can be understood that the surface porous structure or the internal hollow structure is affected by the size of the graphite. Therefore, when the size of the graphite is nanometer-scale, the porous structure of the ceramic particles should also be nanometer-scale, which is the porous structure nanoceramics 141.

[0039] Second, please refer to Figure 2The present invention further provides a coating slurry 241, including the porous structure nanoceramic 141. In some preferred embodiments of the present invention, the coating slurry 241 is obtained by adding a dispersant S21, adding a thickener S22, adding an adhesive S23, and adding a wetting agent S24 to the porous structure nanoceramic 141. Among them, in some preferred embodiments of the present invention, the dispersant includes one or more of sodium polyacrylate, sodium hexafluorophosphate, sodium silicate, sodium dodecyl sulfate, sodium polymetaphosphate, etc.; in some preferred embodiments of the present invention, the thickener includes one or more of sodium carboxymethyl cellulose, sodium starch phosphate, propylene glycol alginate, etc.; in some preferred embodiments of the present invention, the adhesive includes one or more of styrene-butadiene latex, polyacrylamide, water-based polyacrylate, vinyl acetate, polyvinyl alcohol, and polyethylene oxide; in some preferred embodiments of the present invention, the wetting agent includes one or more of polyether-modified trisiloxane, polyoxyethylene alkylphenol ether, and polyoxyethylene fatty alcohol ether.

[0040] In some preferred embodiments of the present invention, the mass ratio of the porous structure nanoceramic 141 to the dispersant is 100: (0.5-10); the mass ratio of the porous structure nanoceramic 141 to the thickener is 100: (0.1-10); the mass ratio of the porous structure nanoceramic 141 to the adhesive is 100: (1-10); the mass ratio of the porous structure nanoceramic 141 to the wetting agent is 100: (0.01-0.2).

[0041] In some preferred embodiments of the present invention, the porous structure nanoceramic 141 is mixed with the dispersant, the thickener, the adhesive, and the wetting agent, and the mixing order is not limited. The purpose is to obtain a sufficient mixing effect in the process. For a better mixing effect, each step such as adding a dispersant S21, adding a thickener S22, adding an adhesive S23 or adding a wetting agent S24 further includes a corresponding mixing action. The mixing action includes stirring, etc. Similarly, the order of the mixing action, whether multiple mixing actions are performed simultaneously, or whether there are other mixing actions are not limited. Preferably, in the step of adding the dispersant S21, the mixing action includes stirring at 1500-3000 rpm for 20-60 minutes; in the step of adding the thickener S22, the mixing action includes stirring at 300-3000 rpm for 20-60 minutes; in the step of adding the adhesive S23, the mixing action includes stirring at 300-1000 rpm for 20-300 minutes; in the step of adding the wetting agent S24, the mixing action includes stirring at 300-800 rpm for 10-30 minutes.

[0042] In a third aspect, the present invention further provides a battery separator, see Figure 2 and Figure 3 , including the porous structure nanoceramic 141 or the coating slurry 241.

[0043] In some preferred embodiments of the present invention, a coating machine is used to coat the coating slurry 241 on one side of a base film at a coating line speed to form a coating, and then the base film and the coating are dried to obtain the battery separator, wherein the coating machine includes a micro-gravure coater. In some preferred embodiments of the present invention, the coating line speed is not limited, but the coating must be uniform; more specifically, preferably, the coating line speed is 10-200 m / min, and the coating thickness is 0.5-5 microns.

[0044] Please refer to Figure 3 The present invention is described below through examples and comparative examples.

[0045] Embodiments 1 to 12 at least include the following steps: porous structure nano-ceramic preparation S1, coating slurry preparation S2, and battery separator preparation S3:

[0046] The porous structure nano-ceramic preparation S1 includes the following steps S11-S14 in sequence.

[0047] Mixing step S11: prepare a metal salt solution 02 with a concentration of 1 mol / L under the following conditions: 50° C., stirring speed of 1500 rpm, and ultrasonic frequency of 15 kHz, so that the metal salt is fully dissolved and mixed completely. On the other hand, spherical nanographite and linear nanographite (spherical nanographite: diameter 2-50 nanometers; linear nanographite: linear length 0.1-2 micrometers) are mixed in a weight ratio of 1:1, and then added to the metal salt solution 02 in a ratio relative to the metal salt. Under the conditions of 35° C., stirring speed of 1500 rpm, and ultrasonic frequency of 15 kHz, the spherical or linear nanographite is evenly dispersed in the metal salt solution 02 to obtain a mixed solution 111.

[0048] Precipitation step S12: Under the conditions of 35° C., a stirring speed of 1500 rpm and an ultrasonic frequency of 7.5 kHz, sodium hydroxide is added to the mixed solution 111 as a pH regulator to adjust the pH value to 8.5. After a reaction time of 15 minutes, the metal cations in the solution are precipitated and a metal precipitate 121 can be obtained after collection.

[0049] Drying step S13: placing the metal precipitate 121 in a forced air drying oven at 100° C. for 2 hours to obtain a metal dried product 131 .

[0050] Calcination step S14: calcining the metal dried product 131 in a muffle furnace under an oxygen atmosphere with an air concentration of 1.5 %. Figure 1 :

[0051] First calcination S141: heating to a first calcination temperature of 200° C. at 5° C. per minute, and maintaining at this temperature for 1 hour (first calcination time);

[0052] Second calcination S142: Raise the temperature to a second calcination temperature of 600° C. at a rate of 10° C. per minute and keep at this temperature for 3 hours (second calcination time); obtain a porous structure nano-ceramic 141 in powder form.

[0053] The coating slurry is prepared in S2, which includes the steps S21-S24 in sequence, please refer to Figure 2 .

[0054] In the following steps, the mass of the porous structure nano-ceramic 141 is set to 100 as the basis for the relevant mass ratio, and the purpose of the following mixing and stirring actions is to achieve uniformity, which is not particularly limited.

[0055] Adding dispersant S21: taking the porous structure nanoceramic 141 and the dispersant and mixing them to obtain the first solution 211; wherein the mass ratio of the porous structure nanoceramic 141 to the dispersant is 100:2, the dispersant is sodium polyacrylate, and the mixing includes stirring at a stirring speed of 2000 rpm for 45 minutes.

[0056] Adding thickener S22: taking the first solution 211 and the thickener and mixing them to obtain the second solution 221; wherein the mass ratio of the porous structure nanoceramic 141 to the thickener is 100:1, the thickener solution is sodium carboxymethyl cellulose, and the mixing includes stirring at a stirring speed of 2000 rpm for 45 minutes.

[0057] Adding adhesive S23: taking the second solution 221 and mixing with the adhesive to obtain the third solution 231; wherein the mass ratio of the porous structure nanoceramic 141 to the adhesive is 100:5, the adhesive is styrene-butadiene latex, and the mixing includes stirring at a stirring speed of 500 rpm for 90 minutes.

[0058] Adding wetting agent S24: taking the third solution 231 and mixing with the wetting agent to obtain the coating slurry 241; wherein the mass ratio of the porous structure nanoceramic 141 to the wetting agent is 100:0.05, the wetting agent is polyether-modified trisiloxane, and the mixing includes stirring at a stirring speed of 500 rpm for 20 minutes.

[0059] Battery separator preparation S3.

[0060] The preparation S3 of the battery separator includes placing the base film on the modified micro-gravure coater, feeding the coating slurry 241 into the feed container of the coater, controlling the line speed to 60 m / min, and using a laser or X-ray thickness gauge to monitor and control the coating thickness online to ensure the uniformity of the coating thickness. The coating thickness is controlled to be 2 μm, and the battery separator is obtained after drying and winding.

[0061] Please refer to Table 2 below. The difference between Examples 1 to 8 is that the metal salt solution 02 used in the mixing step S11 is different.

[0062] Please refer to Table 2 below. Examples 9 to 16 correspond to Examples 1 to 8 respectively in terms of the type of metal salt and the mass ratio of graphite to metal salt. However, in the calcination step S14, there is a third calcination S143, which is subsequent to the second calcination S142. The calcination process is changed to a carbon dioxide atmosphere. The third calcination temperature is 950°C and is kept at this temperature for 30 minutes.

[0063] Please refer to Table 1 and Table 2 below. Compared with Example 1, Example 17 has the same type of metal salt, but a different mass ratio of graphite to metal salt. In addition, compared with Example 2, Example 18 has the same type of metal salt, but a different mass ratio of graphite to metal salt.

[0064] Please refer to Table 2 below. Comparative Example 1 does not include the porous structure nanoceramic preparation S1, and the porous structure nanoceramic 141 to which the dispersant S21 is added is replaced by aluminum chloride ceramic, wherein the aluminum chloride ceramic is in powder form.

[0065] Please refer to Table 2 below. Comparative Example 2 does not include the porous structure nanoceramic preparation S1, and the porous structure nanoceramic 141 with added dispersant S21 is replaced by magnesium chloride ceramic, wherein the magnesium oxide ceramic is in powder form.

[0066] Please refer to Table 2 below. Comparative Example 3 does not include the porous structure nanoceramic preparation S1, and the porous structure nanoceramic 141 to which the dispersant S21 is added is replaced by alumina ceramic, wherein the alumina ceramic is in powder form.

[0067] The above embodiments and comparative examples were tested for efficacy in the following manner:

[0068] As for the thickness of battery separator, the test was carried out using Millimar C1208 film thickness gauge (Millimar C1208, Germany, Millimar Company), and its test standard was GB / T 6672-2001.

[0069] In terms of the determination of impurity elements, inductively coupled plasma mass spectrometry (ICP-MS) is used for testing, and its testing standard is GB / T 30903-2014. The specific testing steps are: prepare a mixed metal ion solution with a metal ion concentration of 0.002 mol / L, wherein the metal ions include iron, cobalt, nickel or manganese; immerse the battery diaphragm to be tested in the mixed metal ion solution at 60°C for 6 hours; after immersion for 6 hours, dry the battery diaphragm and test it using ICP-MS.

[0070] Table 1 shows the types of metal salts and the mass ratio of graphite to metal salts in Examples 1-8 and Examples 17-18. It can be seen that the difference between Examples 1-8 is that in the mixing step S11, the types of metal salts in the metal salt solution 02 are different, and the mass ratios of spherical or linear nanographite to metal salts are different.

[0071] Table 1

[0072]

[0073] Table 2 is a comparison of the preparation methods of various embodiments and comparative examples.

[0074] Table 2

[0075]

[0076] Table 3 shows the efficacy test results of various embodiments and comparative examples. Table 3 mainly compares the ion conductivity and metal ion adsorption concentration of various embodiments and comparative examples.

[0077] Table 3

[0078]

[0079] Regarding the above-mentioned embodiments and comparative examples, it should be first known that the ionic conductivity of all embodiments is higher than that of the comparative example, and the reason for this should include the use of porous structure nanoceramics 141 in the coating slurry of the battery separator; it can also be found that the metal ion adsorption concentration of all embodiments is higher than that of the comparative example, or in other words, the sum of the above-mentioned four metal ion adsorption concentrations (total amount of metal ion adsorption) is higher than that of the comparative example.

[0080] More specifically, by comparing Example 1 with Comparative Example 1, it can be seen that: under the same metal salt conditions, the battery separator coating slurry raw material having porous structure nanoceramics 141 has higher ionic conductivity and metal ion capture than general ceramics.

[0081] By comparing Examples 1 to 8 with Examples 17 to 18, it can be seen that in fact, the mass ratio of graphite to metal salt should be within a certain ratio to achieve better ionic conductivity.

[0082] By comparing Example 1 and Example 3, it can be known that when the metal salt is also aluminum chloride, the ionic conductivity of Example 3 is higher than that of Example 1. The reasons may include that the ratio of template molecules to metal salt in Example 3 is higher than that in Example 1. It can be imagined that more pores will be formed on the surface of the porous structure nanoceramic 141 of Example 3, resulting in a higher adsorption amount of metal ions by the porous structure nanoceramic 141, making the ionic conductivity of Example 3 higher than that of Example 1.

[0083] On the other hand, by comparing Examples 1-6 with Examples 9-14, it can be seen that, when the type of metal salt and the mass ratio of graphite to metal salt are the same, the third calcination S143 can further increase the ion conductivity.

[0084] From the examples, it can be understood that different ceramic materials formed into porous structures by calcining different metal salts have different adsorption capacities for various metal ions.

[0085] The above is only a preferred embodiment of the present invention and cannot be used to limit the patent protection scope of the present invention; therefore, any simple equivalent changes and modifications made according to the patent protection scope of the present invention and the contents of the specification still fall within the patent protection scope of the present invention.

Claims

1. A method for preparing porous nano-ceramics, characterized in that: The following steps are involved: a precipitation step: precipitating a template molecule and a metal salt in a solution to generate a metal precipitate, wherein the template molecule comprises nanographite or carbon nanotubes, the metal salt comprises aluminum salt, calcium salt, magnesium salt, barium salt, zirconium salt or any combination thereof, the metal salt is a metal chloride salt, a metal nitrate salt or any combination thereof, and the mass ratio of the template molecule to the metal salt is 1:(1000-4500); a drying step: drying the metal precipitate to obtain a metal dried product; and A calcination step: performing a first calcination and a second calcination on the metal dried object in an oxygen atmosphere, and then performing a third calcination on the metal dried object in a carbon dioxide atmosphere to obtain a porous structure nanoceramic, wherein the first calcination is to calcine the metal dried object at 100-300° C. for 0.5-3 hours, the second calcination is to calcine the metal dried object at 400-800° C. for 2.5-8 hours, and the third calcination is to calcine the metal dried object at 800-1000° C. for 0.25-2 hours.

2. The preparation method according to claim 1, characterized in that The template molecules are spherical template molecules and / or linear template molecules, wherein the diameter of the spherical template molecules is 2-50 nanometers, and the length of the linear template molecules is 0.1-2 micrometers.

3. The preparation method according to claim 2, characterized in that: The metal salt is aluminum chloride, calcium chloride, zirconium nitrate or any combination thereof.

4. The preparation method according to claim 1, characterized in that: The pH of the solution is 7-12.

5. A coating slurry, characterized in that: The porous structure nano-ceramic is prepared by the preparation method according to any one of claims 1 to 4.

6. A battery separator, characterized in that: It includes: A ceramic layer, wherein the ceramic layer has a porous structure nanoceramic prepared by the preparation method according to any one of claims 1 to 4.

7. A battery, characterized in that: It has the battery separator as claimed in claim 6.

Citation Information

Patent Citations

  • Three-dimensional nanoporous metal-oxide electrode material of lithium ion battery and preparation method thereof

    CN101937989A

  • Preparation method of three-dimensional graphene

    CN103910356A